Immunotherapy in Lung Cancer: A Narrative Literature Review - Hendris Utama Citra Wahyudin; Afriani Afriani; Fenty Anggrainy; Sabrina Ermayanti (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Lung cancer is the most common cause of death from cancer in both men and women worldwide. Cancers with low immunogenicity often do not present antigens, so immune responses can be avoided. Uncontrolled growth of tumor cells occurs due to various factors such as activation of immunosuppressive mechanisms, induction of various immunosuppressive cells, and expression of immune checkpoint molecules. The development of lung cancer management has progressed since the discovery of molecular-based target therapy and immunotherapy. The high expression of tumor mutational burden in lung cancer indicates high immunogenicity in lung cancer. Various immunological mechanisms involving programmed death-1 (PD-1) and programmed death ligand-1 (PD-L1) have been developed for the treatment of lung cancer by utilizing immune system modulation. Nivolumab is the first approved immunotherapy for lung cancer, followed by pembrolizumab, atezolizumab, and durvalumab. The use of immunotherapy involving immune checkpoint inhibitors is an important breakthrough in the management of cancer, including lung cancer. This literature review aimed to describe immunotherapy in lung cancer that focuses on immune checkpoint inhibitors anti-PD-1 and anti-PD-L1.